Analisis Pengaruh Live shopping Terhadap Keputusan Pembelian Konsumen Pada Platform e-commerce di Era Digital - Putri Lailatul Mufarikha (Annusfy : Journal of Multidisciplinary Research, 2026)
This study aims to analyze the influence of live shopping on consumer purchasing decisions on e-commerce platforms in the digital era. The rapid development of digital technology has changed consumer behavior in online shopping through e-commerce platforms. One of the growing digital marketing innovations is live shopping or live streaming commerce, which allows direct interaction between sellers and consumers during product promotion. The research method used is a literature review by examining various previous studies related to live shopping, digital consumer behavior, purchasing decisions, and e-commerce. Data were obtained from scientific journals, articles, and other relevant references accessed through Google Scholar. The results show that live shopping has a significant influence on consumer purchasing decisions. Factors such as direct interaction, consumer trust, promotional strategies including discounts, cashback, flash sales, and free shipping, as well as the communication style of live streaming hosts, play important roles in influencing consumer interest and purchasing decisions.